ANALISIS SARANA DAN PRASARANA PEMBELAJARAN PENDIDIKAN JASMANI SEKOLAH MENENGAH PERTAMA (SMP) DI KECAMATAN NARMADA - Arjun, Apri Aji; Yundarwati, Susi; Yusuf, Putra Muhammad (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2019)
This research is motivated by the unknown knowledge of the facility apparatus and infrastructure of the physical education in junior high school in Narmada district. This study aims to find out the appropriate level of facilities and infrastructure apparatus of physical education in junior high school in Narmada based on Permendiknas No.24 of 2007 about sports facilities and infrastructures. This research is a quantitative descriptive research by survey. The technique of data collection used observation sheet. The population in this study is all junior high schools located in Narmada, amounting to 5 schools. The data analysis conducted in this research is to describe the observation result. The results of the research show that the level of suitability of each school that SMPN 1 Narmada 63,63%. SMPN 2 Narmada 72.72%. SMPN 3 Narmada 45.45%. SMPN 4 Narmada 63.63%. SMPN 5 Narmada 68.18%. SMP Muh 2 Prambanan 9.09%. SMP Muh Boarding School 63.63%. Thus, the conclusion of this research can be stated that the level of suitability of the overall facilities and infrastructure in Junior High SchoolsÂ in Narmada is 61.81%. Â